Influence of remoteness of residence on timeliness of diagnosis and treatment of oral cavity and oropharynx cancer: A retrospective cohort study. Issue 2 (9th February 2020) - Venchiarutti, Rebecca L; Clark, Jonathan R; Palme, Carsten E; Shakespare, Thomas P; Hill, Jacques; Tahir, Abdul Rahim Mohd; Dwyer, Patrick; Young, Jane M
Abstract: Introduction: Geographic disparities in head and neck cancer (HNC) outcomes in Australia may be mediated by timeliness of diagnosis and treatment. This retrospective cohort study examines geographic variations in survival and time intervals leading up to treatment for HNC at two tertiary referral centres in New South Wales. Methods: Eligible patients were NSW residents aged ≥18 years, diagnosed with primary oropharynx or oral cavity squamous cell carcinoma (SCC) between 01 July 2008 and 30 June 2013, and treated with curative intent. Main outcomes were times from diagnosis to treatment and from surgery to post‐operative radiotherapy and overall survival. Differences based on remoteness of residence (regional/remote or metropolitan) were assessed. Results: A total of 224 patients were eligible. Median time from symptom onset to treatment was longer for regional/remote patients with oropharynx SCC (4.7 vs. 3.8 months, P  = 0.044) and oral cavity SCC (6.4 vs. 3.3 months, P  = 0.003). Median time from diagnosis to treatment was longer for regional/remote patients with oropharyngeal SCC (47 days vs. 36 days, P  = 0.003). Time from surgery to adjuvant radiotherapy was longer among regional/remote patients with oral cavity SCC (66 vs. 42 days, P  = 0.001). Overall survival did not differ based on remoteness. Conclusion: Regional/remote HNC patients experienced longer times to diagnosis and treatment, and regardless of remoteness of residence, fewer than half of patients were treated within guideline recommended timeframes. Despite this non‐adherence to guidelines, there were no differences in survival outcomes among this cohort. However, the impact of not meeting guidelines on patient outcomes other than survival warrants further investigation.